Development and validation of wear models by using innovative three-dimensional laser scanners. (August 2019) - Butini, E; Marini, L; Meli, E; Rindi, A; Valigi, MC; Logozzo, S
One of the main problems in railway and tramway systems, both dynamically (safety, comfort etc.) and economically (planning of maintenance interventions, reduction of wheel and rail lifetime etc.), is represented by the wear of wheel and rail profiles, due to the wheel–rail interaction. The profile's shape variation caused by wear influences the dynamic behaviour of the vehicle and, in particular, the wheel–rail contact conditions. Hence, nowadays, one of the most important topics in the railway field is the development of reliable wear models to predict profiles evolution, together with the use of more efficient and accurate measuring instruments for the model validation and the rolling components inspection. In this context, the aim of this research work is the development and the validation of wear models, using experimental data acquired through an innovative measuring instrument based on noncontact three-dimensional laser scanning technology. The tramway line of the city of Florence, characterized by very narrow curves and critical in terms of wear, has been chosen as a reference test case. Moreover, the inspection procedures currently adopted on this line for the maintenance plan are based only on classical two-dimensional contact measurement systems, not so accurate for a complete wear assessment. Therefore, the introduction of a new three-dimensional laser scanning technology may have a great impact on the maintenance management of the line.